College students’ perceived teaching presence in emergency remote online mathematics teaching - Taley, Isaac Bengre (Universitas Muhammadiyah Surakarta, 2022)
In this period of the Covid-19 outbreak, the interest in replacing conventional face-to-face teaching with online teaching in Ghana's Colleges of Education has sown amidst concerns about the presence of teaching. Through an online survey, 452 students from three education colleges responded to the teaching presence scale. This study examined college students' perception of mathematics teaching presence and how gender and the mode of interaction affected students' sense of teaching presence during the emergency remote online teaching of mathematics. The results showed that about 82.7% of the students had a moderate to a high sense of mathematics teaching presence in the emergency remote online teaching. This means that mathematics teachers were unable to identify the mathematics learning needs, neither were teachers able to manage collaborative and reflective work, nor averted undirected discourse among 27.3% of the students. Although the gender of students did not affect the sense of mathematics teaching, the result indicated that in the absence of asynchronous mode of interaction, synchronous and blended modes of interaction positively affected students' perceived mathematics teaching presence. Altogether, this study urges mathematics teachers to employ creative pedagogical approaches that make teaching presence more conspicuous to students in emergency remote online mathematics teaching.